Workshop Pemanfaatan Sampah Rumah Tangga Menjadi Produk Eco Enzyme, Sabun Cuci Piring dan Lilin di Desa Trayu - Arina Manasikana Bintoro; Pujiastuti, Anasthasia; Abdul Roni; Gagah Dwi Wicksono (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2024)
Trayu Village has a relatively large population, and each resident produces household waste. The large amount of household waste is one of the problems in Trayu Village because it can affect health, cleanliness and comfort. The purpose of this community service activity is to increase public knowledge about the use of household waste into useful products. Community service activities were carried out in Trayu Village with PKK mothers as participants. The activity was carried out offline and began with the distribution of pretest questionnaires, counseling on waste management, making products from household waste, and ended with the distribution of posttest questionnaires. The products made include eco enzyme with the main ingredients of fresh vegetable and fruit waste, dishwashing soap using eco enzyme, and candles with used cooking oil as the main ingredient. Based on the results of the workshop activities and the analysis of the pretest and posttest results, it was found that the level of understanding of the training participants increased by 90%. It can be concluded that the knowledge of the training participants increased significantly.   ABSTRAK Desa Trayu memiliki jumlah penduduk yang relatif besar, dan setiap warga menghasilkan sampah rumah tangga. Banyaknya sampah rumah tangga menjadi salah satu permasalahan di Desa Trayu karena dapat mempengaruhi kesehatan, kebersihan dan kenyamanan. Tujuan dari kegiatan pengabdian masyarakat ini yaitu meningkatkan pengetahuan masyarakat tentang pemanfaatan sampah rumah tangga menjadi produk yang bermanfaat. Kegiatan pengabdian masyarakat yang dilakukan di Desa Trayu dengan peserta ibu-ibu PKK. Kegiatan dilakukan secara offline dan dimulai dengan pembagian kuesioner pretest, penyuluhan tentang pengelolaan sampah, pembuatan produk berbahan dasar sampah rumah tangga, dan diakhir dengan pembagian kuesioner postets. Produk yang dibuat meliputi eco enzyme dengan bahan utama sisa sayur dan buah segar, sabun cuci piring menggunakan eco enzyme, dan lilin dengan bahan dasar minyak jelantah. Berdasarkan hasil kegiatan workshop dan d analisis dari hasil pretest serta post test diketahui bahwa tingkat pemahaman peserta pelatihan mengalami peningkatan sebesar 90%. Hal ini dapat disimpulkan pengetahuan peserta pelatihan meningkat secara singnifikan.